2013
DOI: 10.1186/2193-1801-2-628
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pain originating from intra-articular structures of the knee joint in patients with medial knee osteoarthritis

Abstract: PurposeAlthough disease progression of osteoarthritis has been well documented, pain pathophysiology is largely unknown. This study was designed with two purposes: 1) to characterize patients with knee pain predominantly originating from intra-articular structures and 2) to describe the location and pattern of their pain.Materials and methods103 patients with medial knee osteoarthritis underwent an intra-articular injection of local anesthetics (joint block). At least 70% pain relief was defined as positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Although distribution patterns of pain in knee OA varies from ‘localized’ to ‘widespread’ among patients (Ikeuchi et al., ), localized medial knee pain is generally the most frequent observation. In 103 varus knee OA patients, the incidence of anteromedial knee pain during walking and joint motion was 82 and 58%, respectively (Ikeuchi et al., ). Thompson et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although distribution patterns of pain in knee OA varies from ‘localized’ to ‘widespread’ among patients (Ikeuchi et al., ), localized medial knee pain is generally the most frequent observation. In 103 varus knee OA patients, the incidence of anteromedial knee pain during walking and joint motion was 82 and 58%, respectively (Ikeuchi et al., ). Thompson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although distribution patterns of pain in knee OA varies from 'localized' to 'widespread' among patients (Ikeuchi et al, 2013), localized medial knee pain is generally the most frequent observation. In 103 varus knee OA patients, the incidence of anteromedial knee pain during walking and joint motion was 82 and 58%, respectively (Ikeuchi et al, 2013). Thompson et al also reported that the frequency of localized medial knee pain and lateral knee pain was 56 and 43%, respectively, in 799 knee OA patients (Thompson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…formation. It often causes joint pain, swelling and dysfunction, which can affect patients' quality of life, and may lead to depression (1).…”
mentioning
confidence: 99%
“…As an example, inversion injuries of the ankle (lateral ankle sprains) can cause injury to the superficial peroneal nerve, resulting in persistent pain and CRPS symptoms [41]. Pain from degenerative joint disease (DJD) may not be purely due to intra-articular pathology therapies [42], as evidenced by the knee pain relief seen with injection and denervation of the infrapatellar saphenous nerve [43,44]. As little a 6% stretch of a nerve can cause permanent injury [45].…”
mentioning
confidence: 99%